Hybrid Method of Transurethral Resection of Ejaculatory Ducts Using Holmium:Yttriumaluminium Garnet Laser on Complete Ejaculatory Duct Obstruction - Lee, Joo Yong (Yonsei University College of Medicine, 2013)
A 32-year old single man presented with azoospermia and low semen volume which was noted one and half a year ago. Transrectal ultrasonography and seminal vesiculography were performed to evaluate ejaculatory duct obstruction, and transurethral resection of the ejaculatory duct was performed using a hybrid technique of holmium:yttriumaluminium garnet laser with monopolar transurethral resection to overcome the narrow prostatic urethra. To our knowledge, this is the first report on the successful outcome of a hybrid technique applied for transurethral resection of the ejaculatory duct.